Efforts to Prevent Bureaucratic Corruption Based on the Piercing Principles of the Governance Veil in Realizing Good Governance and Clean Governance in Indonesia - Junaedi Junaedi (Journal La Sociale, 2020)
The purpose of this study explains the principle of piercing the governance veil can support the realization of good governance and clean governance in order to prevent the misuse of corruption. The research method is a normative legal method with a statutory approach), concepts and cases. The results of this study can be explained that the principle of piercing the governance veil supports the realization of good governance and clean governance in order to prevent abuse of the power of the authorities (governors / regents / mayors) so as to prevent unlawful acts carried out by the executive as the holder of the people's mandate. The governance veil principle can limit or prevent illegal actions carried out by the government and its staff for personal gain or enrich oneself and its cronies. The conclusion of this study is that due to the legal principles of the governance veil, it can lead to KKN and the occurrence of abuse of authority, resulting in state losses, then criminal penalties based on Law No. 20 of 2001 concerning criminal acts of corruption.